Learner Corpora and Corpus-Informed Teaching Materials for Economy faculty students - Ismoilova Zarifa; Nasriddinova Nasiba (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
to date, for languages such as English, large diversifications have been created fixed and representative annotated corpora for teaching students of Economy faculty. However, none the corps is unable to serve all purposes at once. Therefore, the creation on the basis of universities of specialized methodologically-oriented language corpus is becoming a daily practice.